Primary CNS Burkitt Lymphoma: A Case Report of a 55-Year-Old Cerebral Palsy Patient - Kathryn Bower; Nilay Shah (Case Reports in Oncological Medicine)
With primary central nervous system lymphoma (PCNSL) being a rare disease, the subtype of Burkitt lymphoma (BL) presenting as a sole CNS lesion is an even more exceptional diagnosis. A case of coexistent primary CNS Burkitt lymphoma (PCNSBL) with cerebral palsy (CP) is presented. A 55-year-old Caucasian male presented with increasing bilateral lower extremity weakness above his baseline in addition to signs of increased intracranial pressure. Four abnormal enhancing masses were detected on MRI with biopsy results consistent with Burkitt lymphoma. Complete staging workup was completed with no evidence of extra-CNS disease noted on PET/CT, bone marrow biopsy, or cerebral spinal fluid analysis. The patient was treated with intravenous as well as intrathecal chemotherapy and found to be in a complete remission at six months. Recurrence in the CNS was observed four months later with treatment consisting of whole brain radiation as well as intrathecal chemotherapy. Thirty months after diagnosis, the patient remains disease-free. To our knowledge, this is the first case of PCNSBL in the setting of CP. A review of literature regarding treatment options in this controversial setting is provided.